EFEKTIFITAS PENGGUNAAN APLIKASI ANDROID TUMBUH KEMBANG ANAK SEBAGAI SARANA PEMANTAUAN SECARA MANDIRI OLEH MAHASISWA PRODI DIII KEBIDANAN - Feby Alfy (Universitas Prima Indonesia, 2024)
Growth and development are two different events but cannot be separated. Every family hopes that their children will grow optimally in the future. . About 95% of children with developmental disabilities live in low- and middle-income countries. Nationally in Indonesia, the prevalence of nutritional status for children under five consists of 3.9% poor nutrition, 13.8% undernutrition, 79.2% good nutrition and 3.1% overnutrition. Therefore, it is important to monitor children's growth and development and there are many cases related to growth and development disorders. The result of the p value is 0.000 < 0.005, there is an influence of the use of the Android growth and development application on the results of monitoring the growth and development of children aged 0-5 years by students of the DIII Midwifery Study Program at STIKes Salewangang Maros. It is hoped that students and parents will be able to carry out regular monitoring of their children's growth and development independently using an Android application or visiting health facilities.